A novel hydrated salt-based phase change material for medium- and low-thermal energy storage. (1st July 2023) - Hu, Yige; Wang, Hang; Chen, Hu; Ding, Yang; Liu, Changtian; Jiang, Feng; Ling, Xiang
Abstract: Magnesium nitrate hexahydrate (MNH) was considered as a promising medium- and low-temperature phase change material (PCM) owing to high latent heat, weak corrosion, and low price. While supercooling performance greatly restricted the application of such PCM. In this work, MNH-based composite PCM containing a novel nucleating agent was prepared. Supercooling behavior and thermophysical properties of composites were analyzed. Additionally, thermal performance of composites in a fin-plate heat storage unit was investigated. Results showed that 2 wt% magnesium sulfate heptahydrate (MSH) effectively suppressed supercooling performance and was chemically compatible with MNH. Composites containing 2 wt% MSH and 2 wt% sodium carboxymethyl cellulose (CMC) performed favorable thermal properties, including supercooling degree of 0.6 °C, phase change temperature of 89 °C, latent heat of 166.88 J/g, and heat storage density of 220.78 J/g. Effective working temperature of the composite should be no more than 140 °C. Magnesium sulfate tetrahydrate (MST) was actually the real component in MSH that inhibited the supercooling of MNH. Compared with paraffin, encapsulated MNH-based composite PCM with a 6720 kJ higher heat storage capacity possessed a much shorter charging/discharging time due to the higher thermal conductivity. The results might provide a foundation for the practical application of MNH. Highlights: A novel MNH-based composite PCM with good thermophysical properties were prepared. MSH was firstly demonstrated to be an effective nucleating agent for MNH. Effective working temperature of the composite PCM should be no more than 140 °C. Thermal performance of composite PCM in a fin-plate heat storage unit was analyzed.